Perfil clínico e laboratorial de pacientes positivos para BCR-ABL1 no estado do Amazonas - Costa, Thainá Cristina Cardoso (2020)
Currently, it is known that Chronic Myeloproliferative Neoplasms (MPNs) are associated with clonal abnormalities, one of which is BCR-ABL1. The oncoprotein BCR-ABL1 is the result of a reciprocal translocation of chromosomes 9 and 22 and has a constitutive tyrosine kinase (TK) activity. Common in over 95% of patients with chronic myeloid leukemia, it can also be present in other NPMs. Although there are national and international scientific studies on the frequency of BCR-ABL1 in MPN patients, no research was found in the literature regarding the distribution and types of BCR-ABL1 transcripts in the region of the state of Amazonas. Objectives: To describe the clinical, laboratory and main comorbidities of patients positive for qualitative BCR-ABL1 p210 treated at the HEMOAM Foundation. Material and Methods: A retrospective and cross-sectional study was carried out, using clinical and laboratory data from 135 patients under suspicion of chronic myeloid leukemia, seen at HEMOAM. The MannWhitney test was used to compare the groups studied. For the survival analysis, the Kaplan- Meier method (log-rank test) was used to demonstrate the time of death in 16 months after the result of the qualitative examination for BCR-ABL1. Results: The 135 patients studied, 97 (71.9%) were positive for BCR-ABL1, 29 (21.5%) negative for BCR-ABL1 and 9 (6.6%) samples from patients who did not present - if satisfactory for the analysis. 71 (56.3%) patients were male and 59 (43.7%) female. The mean age between the groups was around 48.95 ± 19.24 (BCR-ABL1 +) and 53.41 ± 17.43 (BCR-ABL1-). It was also noted that the transcript b3a2 (63.9%) was the most frequent, followed by the transcript b2a2 (32%), b3a3 (2.1%), b3a2 /b2a2 (1%) and b3a2 / b3a3 (1%). It was observed in the hematological and biochemical profile that leukocytes (p <0.0077), blasts (p <0.0140), promyelocytes (p <0.0478), metamyelocytes (p <0.0290), neutrophil rod (p < 0.0061), basophils (p <0.0027) and platelets (p <0.0352) were significantly higher in BCR-ABL1 + patients compared to BCR-ABL1- patients. In the analysis between the transcripts b3a2 and b2a2, a statistically significant increase was observed in the percentage of myelocytes (p <0.0181) and metamyelocytes (p <0.0256) in the b3a2 group in relation to the b2a2 group. As for the other variables in the profiles, there were no notable statistical differences in all groups studied. Regarding the presence of comorbidities, Arterial Hypertension and Diabetes Mellitus were the most frequent in all studied groups. We did not observe statistical significance when comparing the groups BCR-ABL1 + and BCR-ABL1- in the analysis of survival. Conclusion: The b3a2 transcript is the most frequent within the population of BCR-ABL1-positive patients in the state of Amazonas and seems to be more associated with a higher leukocyte profile (myelocytes and metamyelocytes), since it has a lower tyrosine kinase activity than the b2a2 transcript. In addition, systemic arterial hypertension and diabetes mellitus seem to be more frequent in these patients